The Development of Core Competencies at Higher Education: A Suggestion Model for Universities in Indonesia - Hadiyanto, Hadiyanto (EDUCARE, 2010)
ABSTRACT: Developing graduate core competencies in higher education has been becoming an actual and trend issue due to the greatest concerns of students, governments, and employers about the quality of higher education outcomes. Higher education in Indonesia should turn the policies and the curriculum of university from conventional objective to recent contexts of global changes and employment settings. University must develop a curriculum which is not only aim to develop studentsâ knowledge but also to develop studentsâ core competencies, namely communication skill, IT (Information and Technology) skill, numeracy, learning how to learn, problem solving, working with others, and subject content competencies. The frameworks of core competencies development should be formulated and implemented and graduate âcore competencesâ must become a measurement of quality to face the global competition. By this manner, intended outcomes of higher education namely employability, lifelong learning, and good citizenship will be attained. In other words, the universities in Indonesia should envisage that every single graduate of the university posses the seven attributes. The seven skills could be carried out in delivering course content. Finally, by equipping students with the core competencies they will succeed as professionals and responsible members of society. KEY WORDS: Core competencies, higher education in Indonesia, policies and curriculum of the university, and global competition.Â About the Author: Hadiyanto is a Lecturer at the Faculty of Teacher Training and Education UNJA (Universitas Negeri Jambi or State University of Jambi) in Sumatera, Indonesia. He can be reached at: hadi_tesl05@yahoo.comHow to cite this article? Hadiyanto. (2010). âThe Development of Core Competencies at Higher Education: A Suggestion Model for Universities in Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.3(1) August, pp.11-22. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 9, 2010); Revised (July 17, 2010); and Published (August 17, 2010).